Global Purchasing Power Parities and Real Expenditures : 2005 International Comparison Program - World Bank (Washington, DC, 2015)
The International Comparison Program (ICP) is a worldwide statistical initiative to collect comparative price data and estimate purchasing power parities (PPPs) of the world's economies. Using PPPs instead of market exchange rates to convert currencies makes it possible to compare the output of economies and the welfare of their inhabitants in real terms (that is, controlling for differences in price levels). This report brings together the results of two separate PPP programs. The first is the global ICP program conducted by the ICP global office within the World Bank, which provided overall coordination for the collection of data and calculation of PPPs in more than 100 (mostly developing) economies. The program was organized into five geographic areas: Africa, Asia-Pacific, Commonwealth of Independent States, South America, and Western Asia. Regional agencies took the lead in coordinating the work in the five regions. In parallel, the Statistical Office of the European Communities (Eurostat) and the Organization for Economic Co-operation and Development (OECD) conducted their 2005 PPP program, which comprised 46 economies. Eurostat covered 37 economies: the 25 European Union (EU) member states; the European Free Trade Association (EFTA) economies (Iceland, Norway, and Switzerland); and Albania, Bosnia-Herzegovina, Bulgaria, Croatia, Macedonia, Montenegro, Romania, Serbia, and Turkey. The OECD part of the program included 9 other economies: Australia, Canada, Israel, Japan, the Republic of Korea, Mexico, New Zealand, the Russian Federation, and the United States. The main reasons for conducting the ICP on a regional basis are that the products to be priced are more homogeneous within regions, the expenditure patterns are likely to be more similar, and language differences are reduced. Moreover, dividing the ICP organization among a number of regional offices in relatively close proximity to the economies they are coordinating provides operational benefits.